Beyond Evidence Based Policy in Public Health - Smith, K. author. aut Link
XVII, 251 p.
Keywords: This book explores the complex relationship between public health research and policy, employing tobacco control and health inequalities in the UK as contrasting case studies. It argues that focusing on research-informed ideas usefully draws attention to the centrality of values, politics and advocacy for public health debates.